The Effect Of Job Insecurity, Distributive Injustice And Workload On Social Loafing Behavior In Hospital Nurses With Turnover Intention As Mediation - Faisal Nur Fahmi; Sri Wahyuni; Suyoto Suyoto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of job insecurity, distributive injustice and workload on social loafing behavior in nurses, with turnover intention as a mediating variable. The phenomenon of social loafing can have a negative impact on the quality of teamwork in hospitals, especially among nurses who work in groups. The research approach was quantitative with 165 nurse respondents at Muhammadiyah Siti Aminah Bumiayu Hospital. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to test the direct and indirect influence of the variables studied. The results of the study show that the variables of job insecurity, distributive injustice and workload influence increasing turnover intention. The distributive injustice variable showed a significant direct influence on social loafing, while job insecurity and workload did not have a significant direct influence. In addition, turnover intention does not have a significant mediating role in bridging the relationship between the three work stressors and social loafing.